Pendidikan Damai sebagai Pendidikan Resolusi Konflik dan Misi Pendidikan Kewarganegaraan untuk Penguatan Toleransi dan Membangun Budaya Damai - Rianda Usmi (Departement of Mathematics Education, 2024)
This research aims to describe (1) the conceptualization of peace education as conflict resolution education and the mission of citizenship education and (2) the realization of peace education to strengthen tolerance and build a culture of peace. This research uses a qualitative descriptive approach with a literature study method. The research results show that (1) the conceptualization of peace education as resolution education and the mission of citizenship education is an educational process based on a philosophy that teaches non-violence, love, compassion, trust, justice, and cooperation of all mankind. Peace education is education with several values, beliefs, traditions, behaviors, and lifestyles based on the principles of non-violence, tolerance, solidarity, respect for human rights and freedom; (2) the realization of peace education to strengthen tolerance and build a culture of peace can be realized in three domains, namely; first, macro (government policy); second, meso (school institutions, family/community); third, micro (curriculum). Peace education can be internalized and taught to society through these three domains.